The Brain from Within - di Porzio, Umberto (Frontiers in Human Neuroscience, 2016)
Functional magnetic resonance imaging (fMRI) provides a powerful way to visualize brain functions and observe brain activity in response to tasks or thoughts. It allows displaying brain damages that can be quantified and linked to neurobehavioral deficits. fMRI can potentially draw a new cartography of brain functional areas, allow us to understand aspects of brain function evolution or even breach the wall into cognition and consciousness. However, fMRI is not deprived of pitfalls, such as limitation in spatial resolution, poor reproducibility, different time scales of fMRI measurements and neuron action potentials, low statistical values. Thus, caution is needed in the assessment of fMRI results and conclusions. Additional diagnostic techniques based on MRI such as arterial spin labeling and the measurement of diffusion tensor imaging provide new tools to assess normal brain development or disruption of anatomical networks in diseases. A cutting edge of recent research uses fMRI techniques to establish a “map” of neural connections in the brain, or "connectome". It will help to develop a map of neural connections and thus understand the operation of the network. New applications combining fMRI and real time visualization of one's own brain activity (rtfMRI) could empower individuals to modify brain response and thus could enable researchers or institutions to intervene in the modification of an individual behavior. The latter in particular, as well as the concern about the confidentiality and storage of sensitive information or fMRI and lie detectors forensic use, raises new ethical questions.